206k views
2 votes
Solve for x: 3(x + 1) = −2(x − 1) − 4

Group of answer choices:
1
−1
−5
−25

User Smont
by
5.2k points

2 Answers

7 votes
-1

3(x+1)= -2(x-1)-4
3x+3 =-2x-2
-3 -3
3x = -2x-5
+2x = +2x
5x = -5
5x/5 = -5/5
X = -1
User Franssu
by
5.4k points
0 votes

Answer:

x = -1

Answer choice B. -1 is correct

Explanation:

3(x + 1) = −2(x − 1) − 4

3x + 3 = -2x + 2 - 4

3x + 3 = -2x - 2

-3 -3

-------------------------------

3x = -2x - 5

+2x +2x

--------------------------------

5x = -5

/5 /5

--------------------------------

x = -1

User Fazeleh
by
4.7k points